HABEAS CORPUS AND WRIT OF MANDAMUS IN ADMINISTRATIVE DISCIPLINARY PROCEEDINGS - Martins Sant’ Anna, Matheus (Revista Gênero e Interdisciplinaridade, 2025)
This study aims to analyze the use of habeas corpus (HC) and writs of mandamus (MS) in administrative disciplinary proceedings (PAD), outlining the constitutional foundations, legal framework, eligibility requirements, limits, and strategies for choosing the appropriate avenue. It draws on articles 5, LXVIII, LXIX, and LV of the Constitution, as well as Law 12.016/2009 and administrative law legislation, to situate the issue within the system of guarantees and control of the legality of state acts. The HC is examined as a remedy aimed at the immediate protection of freedom of movement, including in exceptional circumstances in the PAD, and the MS as an instrument for protecting a clear and certain right against illegality or abuse of power, with an emphasis on pre-established evidence, statute of limitations, and effects. Finally, it proposes practical criteria for adequacy and subsidiarity between HC, MS, and annulment actions, preventing the risks of an inappropriate avenue.